1975
DOI: 10.2307/3897234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Germination of Four Common Grass Species of Ujjain (India)

Abstract: Furthermore, they point out that the relationship of germination to acidity varies considerably with the seeds of different plants and with the kind of acids used, organic acids being more favourable than inorganic, when used in equivalent amount. Highlight: The effect of acids and bases on the seedgermination of four important grasses were evaluated at Ujjain fIndia). The specieswere Iseilema anthephoroides, Sehima nervosum, Apluda mutica and Dactyoctenium aegyptium. The seeds were treated in petri dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Henig-Sever et al (1996) and Singh et al (1975) showed that solutions with pH in the range 7-9 reduced germination rates in most plant species and by pH of 10-11, total inhibition was observed in most cases. Singh et al (1975) suggested that the germination rate-response to pH followed a 2 nd order polynomial curve, and therefore, a linear correlation (Pearson) does not describe the relationship between pH and growth response appropriately. Tested on the data from this study, is shows that indeed a 2 nd order polynomial curve fitted very well with the plant response ( Figure 4.5A: R²=0.63, Figure 4.5B: R²=0.68).…”
Section: Growth Suppression Effects Of Biocharsmentioning
confidence: 98%
See 1 more Smart Citation
“…Henig-Sever et al (1996) and Singh et al (1975) showed that solutions with pH in the range 7-9 reduced germination rates in most plant species and by pH of 10-11, total inhibition was observed in most cases. Singh et al (1975) suggested that the germination rate-response to pH followed a 2 nd order polynomial curve, and therefore, a linear correlation (Pearson) does not describe the relationship between pH and growth response appropriately. Tested on the data from this study, is shows that indeed a 2 nd order polynomial curve fitted very well with the plant response ( Figure 4.5A: R²=0.63, Figure 4.5B: R²=0.68).…”
Section: Growth Suppression Effects Of Biocharsmentioning
confidence: 98%
“…Finally, biochar can also contain contaminants which are supplied to soil with biochar. Rosa et al, 2014;Uzoma et al, 2011) locking up of N (Deenik et al, 2010;Nelissen et al, 2014;Prommer et al, 2014;Rondon et al, 2007;Shenbagavalli and Mahimairaja, 2012) binding and immobilisation of organic compounds reduced toxicity of contaminants (Beesley et al, 2011;Buss et al, 2012;Karer et al, 2015;Kim, 2015) reduced efficacy of pesticides (Cabrera et al, 2014;Graber et al, 2012;Jones et al, 2011;Kuppusamy et al, 2016;Yu et al, 2009) increase in soil pH reduced availability and toxicity of several PTEs and increased P availability (Butnan et al, 2015;Deal et al, 2012;Jeffery et al, 2015a;Kloss et al, 2014b) potential germination and plant growth inhibition when pH raised into alkaline range (Jeffery et al, 2015a;Shoemaker et al, 1990;Singh et al, 1975) supply of ash to soil provision of plant nutrients (Hossain et al, 2011;Ippolito et al, 2015) nutrient imbalances and salinity-related issues (Butnan et al, 2015;Domene et al, 2015;Gell et al, 2011;Rajkovich et al, 2012)…”
Section: Mechanisms Of Growth Inhibition Caused By Biocharmentioning
confidence: 99%
“…Henig-Sever et al (1996) and Singh et al (1975) showed that solutions with pH in 535 the range 7-9 reduced germination rates in most plant species and by pH of 10-11, 536…”
mentioning
confidence: 99%
“…total inhibition was observed in most cases. Singh et al (1975) suggested that the 537 germination rate-response to pH followed a 2 nd order polynomial curve, and 538 therefore, a linear correlation (Pearson) does not describe the relationship between 539 pH and growth response appropriately. Tested on our data set, we found that indeed 540 a 2 nd order polynomial curve fitted very well with the plant response ( Figure 3A: R² = 541 0.63, Figure 3B: R² = 0.68).…”
mentioning
confidence: 99%
“…Accordingly, one study suggested that microbial attachment in the rumen is the principle reason for reducing seed germination (Obara et al 2009). On the other hand, although there was individual difference in sensitivity to pH value, generally, grasses cannot germinate at a pH of less than 2.5 (Singh et al 1975). Therefore, the rumen fluids, which are characterized by high microorganism‐ richness and acidity, could lead to a loss of seed germinability, especially in seeds lacking thick coats (Horiguchi et al 2008).…”
Section: Discussionmentioning
confidence: 99%